A stratified therapeutic model incorporated with studies on regulatory B cells for elderly patients with newly diagnosed multiple myeloma. (20th September 2022) - Tang, Wenjiao; Li, Yan; Zou, Zhongqing; Cui, Jian; Wang, Fangfang; Zheng, Yuhuan; Hou, Li; Pan, Ling; Xiang, Bing; Chang, Hong; Zhang, Li; Niu, Ting
Abstract: Objective: Despite the availability of new agents, elderly patients with multiple myeloma (MM) usually present with poor outcomes due to the heterogeneity of disease conditions, especially immune deficiency. Regulatory B cells (Bregs) can be involved in immune defects by exerting immune regulatory functions in MM. In order to provide more evidence‐based practice for the elderly MM, the study established and assessed a stratified therapeutic model with studies on Bregs for Chinese Elderly Multiple Myeloma in 2021 (CEMM2021). Methods: In this open‐label, non‐interventional, prospective study in the real world, 159 newly diagnosed MM (NDMM) patients over 65 years old were sequentially recruited and bone marrow aspirates prior to treatment were obtained to detect the ratios of Bregs by flow cytometry. Results: Based on the CEMM2021 model, 147 patients had received at least one cycle of induction therapy, including bortezomib/dexamethasone (Bd) ( n  = 80), lenalidomide/dexamethasone (Rd) ( n  = 27), Bd with a third agent X (Bd + X) ( n  = 27), and other regimens ( n  = 13). The proportions of patients achieving very good partial response or better were comparable among Bd, Bd + X, and Rd groups (41.9% vs. 54.5% vs. 44.0%, p  = 0.472). Besides, the progression‐free survival (PFS) and overall survival (OS) were not significantly different among Rd, Bd, and Bd + X groups. Multivariable analysis showed that induction efficacy less than partial response (PR) were poor prognostic factors for PFS, while Revised‐International Staging System (R‐ISS) III and efficacy less than PR were poor prognostic factors for OS. This study also found that the ratios of bone marrow Bregs <10% ( p  = 0.036) and SUVmax of PET‐CT scan >4.2 ( p  = 0.000) were closely correlated with OS in the elderly MM. Conclusions: For the elderly NDMM, the CEMM2021 algorithm in our center might provide a valuable reference for the guidance of therapeutic strategies, with the combination of Bregs resulting in an effective and clinically meaningful prediction in contemporary treatment. Abstract : The management of elderly patients with MM remains challenging due to the heterogeneity of disease conditions, especially immune deficiency. In order to provide more evidence‐based practice for the elderly MM, the study established and assessed a stratified therapeutic model with studies on Regulatory B cells for Chinese Elderly Multiple Myeloma in 2021 (CEMM2021).